Differential impact of coffee quantity and sweetening on body composition parameters and inflammation - Annunziata, Giuseppe; Frias-Toral, Evelyn; Campa, Francesco; Antonieta Touriz Bonifaz, Maria; Verde, Ludovica; Galasso, Martina; Savastano, Silvia; Colao, Annamaria; Paoli, Antonio; Simancas-Racines, Daniel; Muscogiuri, Giovanna; Barrea, Luigi (Frontiers in Nutrition, 2025)
BackgroundCoffee is the most consumed and popular beverage worldwide. The health benefits of its regular, moderate consumption are well known, and include antioxidant and anti-inflammatory effects, as well as metabolic effects, reducing the risk of obesity and related diseases. The available literature, however, provides no information about the effect of coffee consumption on body composition (BC) and inflammation. The present cross-sectional observational study aims to investigate the effect of coffee consumption on BC and inflammation-related parameters, as well as the possible impact of adding sugar and the frequency of consumption.MethodsCoffee consumption habits, preference for adding sugar and frequency of daily consumption were assessed in 2,556 adults (1,080 men and 1,476 women). BC was assessed using Bioelectrical Impedance Analysis (BIA), whilst high-sensitivity C-reactive protein (hs-CRP) levels were monitored for inflammatory status.ResultsA total of 1,855 subjects (680 men and 1,175 women) were included in the statistical analysis. Compared to non-consumers, coffee consumers showed lower body mass index (BMI), waist girth (WG), and hs-CRP levels, and higher skeletal muscle mass (SMM), appendicular SMM (ASMM), phase angle (PhA), and standardised PhA (SPA) (p < 0.001 for all). The same trend was observed for unsweetened coffee consumers compared to subjects consuming sweetened coffee. With increasing coffee consumption, BMI, WG, and hs-CRP generally decreased, whilst SMM and ASMM showed a bell-shaped trend with peak values in those consuming 2–3 cups per day. Similarly, PhA and SPA values were highest among moderate coffee consumers.ConclusionThese findings suggest that moderate coffee consumption, particularly unsweetened coffee, is associated with more favourable body composition and inflammatory profiles. Given the observational design, causality cannot be established. Nevertheless, the results may inform dietary guidance aimed at supporting muscle maintenance and mitigating obesity-related metabolic risk.